2021
DOI: 10.1051/0004-6361/202040072
|View full text |Cite
|
Sign up to set email alerts
|

A new, Gaia-based, catalogue of blue straggler stars in open clusters

Abstract: Context. Blue straggler stars are exotic objects present in all stellar environments whose nature and formation channels are still partially unclear. They seem to be particularly abundant in open clusters (OCs), thus offering a unique chance to tackle these problems statistically. Aims. We aim to build up a new and homogeneous catalogue of blue straggler stars (BSS) in Galactic OCs using Gaia to provide a more solid assessment of the membership of these stars. We also aim to explore possible relationships of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
49
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 69 publications
(68 reference statements)
7
49
0
1
Order By: Relevance
“…Upon comparing our 16 BSS candidates with the BSS candidates identified by Rain, Ahumada, & Carraro (2021), we find 9 BSS to be common. 4 BSS candidates identified by Nine et al (2020) and 3 BSS candidates identified by Rao et al (2021) are missing in Rain, Ahumada, & Carraro (2021). Most of their remaining 7 BSS candidates are located beyond 28 from the cluster center, the radius of the cluster as per Rao et al (2021).…”
Section: Bss Candidatesmentioning
confidence: 95%
See 2 more Smart Citations
“…Upon comparing our 16 BSS candidates with the BSS candidates identified by Rain, Ahumada, & Carraro (2021), we find 9 BSS to be common. 4 BSS candidates identified by Nine et al (2020) and 3 BSS candidates identified by Rao et al (2021) are missing in Rain, Ahumada, & Carraro (2021). Most of their remaining 7 BSS candidates are located beyond 28 from the cluster center, the radius of the cluster as per Rao et al (2021).…”
Section: Bss Candidatesmentioning
confidence: 95%
“…Blue straggler stars (BSS) are one of the exotic stellar populations whose evolution differs from normal single stars. They are commonly found in diverse stellar environments such as globular clusters (Sandage 1953;Fusi Pecci et al 1992;Sarajedini 1993), open clusters (Johnson & Sandage 1955;Burbidge & Sandage 1958;Sandage 1962;Rain, Ahumada, & Carraro 2021), dwarf galaxies (Momany et al 2007;Mapelli et al 2009), and galactic fields (Preston & Snedon 2000). There are three fundamental mechanisms that explain the formation of BSS: (a) direct stellar collisions in dynamical interactions in dense stellar environments (Hills & Day 1976), (b) mass transfer in close binary systems (McCrea 1964), and (c) merger or mass transfer of an inner binary in a triple system through Kozai mechanism (Perets & Fabrycky 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The A-F main-sequence stars occupy a small region in the center of the H-R diagram, but have been differentiated into not only δ Sct and γ Doradus (abbreviated as γ Dor) variables (Pollard, 2009;Balona et al, 2011a), but also metallic-line A (Am) (Smalley et al, 2017), peculiar abundance A (Ap) (Mathys et al, 2020), rapidly-oscillating Ap (roAp) (Holdsworth, 2021) stars, α 2 CVn variables (Sikora et al, 2019), λ Boo stars (Murphy and Paunzen, 2017), the High Amplitude δ Sct (HADS) (McNamara, 2000) and SX Phe (Nemec et al, 2017) stars, blue stragglers (Rain et al, 2021), and the maybe "mythical" 1 Maia variables (Breger, 1980;Cox, 1983;Daszyńska-Daszkiewicz et al, 2017;White et al, 2017;Balona, 2018). Kepler observations have revealed overlap and commonalities among these types, pointing the way to a more fundamental understanding of the origins of the diverse phenomena seen in these stars.…”
Section: Introductionmentioning
confidence: 99%
“…Those with an effective temperature of T eff ≥ 10 000 K have spectra that are similar to the much younger population I Btype main-sequence stars but with weaker Helium lines, which can be distinguished spectroscopically (see Figure 1). The main challenge in producing a catalogue of low contamination is differentiating between blue horizontal-branch stars and younger, population I main-sequence A-type and B-type stars as well as blue stragglers, which are older, population II main-sequence stars that have been rejuvenated through acquisition of additional mass (Rain et al 2021) and that display A-type spectra. The additional mass may be gained by Roche Lobe overflow in a close binary system (McCrea 1964), through stellar merger (Hills & Day 1976;Davies et al 1994), or both.…”
Section: Introductionmentioning
confidence: 99%